Gomphonema qingyiensis sp. nov., a new freshwater species (Bacillariophyceae) from Qingyi River, China - Zhang, Lixuan; Yu, Pan; Kociolek, J.p.; Pang, Wanting; Wang, Quanxi; You, Qingmin (Phytotaxa, 2020)
In this study, a new Gomphonema species from Qingyi River, Anhui Province, China, was identified and named Gomphonema qingyiensis sp. nov. We detailed its morphology using light microscopy (LM) and scanning electron microscopy (SEM). The LM and SEM photographs illustrate the size ranges and particular ultrastructure of the new species. The valves of G. qingyiensis are clavate and symmetrical to the apical axis. The headpole is broadly rounded and the footpole is narrowly rounded. The axial area is narrow, linear to linear-lanceolate. The central area is small and rectangular in shape. One stigma is evident. Striae are slightly radiate at the center. Biseriate striae and areolae are clearly evident in the LM images. The new species was compared with G. irroratum, G. zairense, G. dirangense, G. doonensis, G. latistigmata, G stoermeri, G marvanii, G cholnokyi, and G. clavatulum and was found to differ from these species in terms of the valve shape, size, striae density and row number, and central area.